Unravelling the reaction mechanism of matrix metalloproteinase 3 using QM/MM calculations - Feliciano, Gustavo Troiano [UNESP]; Roque da Silva, Antonio José (Elsevier B.V., 2015)
The matrix metalloproteinase family (MMP) constitutes a family of zinc (Zn) proteases that catalyze the breaking of peptide bonds in proteins. These enzymes are very promising drug targets, since they are involved in remodeling and degradation of the extracellular matrix, which is a key process required for cancer metastasis, and thus, their reaction mechanism has been an area of intensive research. Early proposal based on acid base catalyzed hydrolysis, suggested that a conserved zinc bound water molecule acted as the nucleophile attacking the peptide bond carbon, after being activated by essential glutamate. The possibility of a direct nucleophilic attack by the enzyme, performed by the glutamate was also suggested. These are the key yet unsolved issues about MMP reaction mechanism.In the present work, we used hybrid quantum/classical calculations to analyze the structure and energetics of different possible hydrolysis reaction paths. The results support a water mediated mechanism, where both the nucleophile water molecule and the carbonyl oxygen of the scissile peptide bond are coordinated to zinc in the reactive configuration, while the essential glutamate acts as the base accepting the proton from the nucleophilic water. Formation of the carbon-oxygen bond and breaking of carbon-nitrogen bond were found to be concerted events, with a computed barrier of 14.8 kcal/mol. Substrate polarization was found to be important for the observed reaction rhechanistn, and a substantial change in the metal coordination environment was observed, particularly, regarding the zinc-histidine coordination. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Matrix metalloproteins; Enzyme catalysis; QMMM